Polysulfide-Scission Reagents for the Suppression of the Shuttle Effect in Lithium–Sulfur Batteries - Hua, Wuxing; Yang, Zhi; Nie, Huagui; Li, Zhongyu; Yang, Jizhang; Guo, Zeqing; Ruan, Chunping; Chen, Xi’an; Huang, Shaoming (ACS nano, 2017)
Lithium–sulfur batteries have become an appealing candidate for next-generation energy-storage technologies because of their low cost and high energy density. However, one of their major practical problems is the high solubility of long-chain lithium polysulfides and their infamous shuttle effect, which causes low Coulombic efficiency and sulfur loss. Here, we introduced a concept involving the dithiothreitol (DTT) assisted scission of polysulfides into lithium–sulfur system. Our designed porous carbon nanotube/S cathode coupling with a lightweight graphene/DTT interlayer (PCNTs-S@Gra/DTT) exhibited ultrahigh cycle-ability even at 5 C over 1100 cycles, with a capacity degradation rate of 0.036% per cycle. Additionally, the PCNTs-S@Gra/DTT electrode with a 3.51 mg cm–2 sulfur mass loading delivered a high initial areal capacity of 5.29 mAh cm–2 (1509 mAh g–1) at current density of 0.58 mA cm–2, and the reversible areal capacity of the cell was maintained at 3.45 mAh cm–2 (984 mAh g–1) over 200 cycles at a higher current density of 1.17 mA cm–2. Employing this molecule scission principle offers a promising avenue to achieve high-performance lithium–sulfur batteries.